2011
DOI: 10.1038/aja.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of letrozole use for improving spermatogenesis in non-obstructive azoospermia patients with normal serum FSH

Abstract: We investigated whether letrozole (2.5 mg day 21 ) improves sperm count in non-obstructive azoospermia (NOA) patients. Four men were included in this study, and they had folliculo-stimulating hormone and other hormone levels within the normal range and no varicoceles or chromosomal aberrations. These four patients were administered letrozole for 3 months. Sperm count, testicular volume, gonadotropin, testosterone (T) and estradiol (E2) blood levels were assessed before, during and 1 week after the suspension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 13 publications
4
30
2
Order By: Relevance
“…Hormonal differences between pre-and postletrozole administration agree with previous literature, which indicated that letrozole increases sperm count by increasing gonadotrophin, T/E2 and testosterone levels. [2][3][4] Because the literature is in agreement with the data presented here, we can confirm that letrozole increased the sperm count in dispermic patients with T/E2 ,10.…”
Section: Letrozole For Azoospermia and Cryptozoospermia G Cavallini Esupporting
confidence: 81%
See 4 more Smart Citations
“…Hormonal differences between pre-and postletrozole administration agree with previous literature, which indicated that letrozole increases sperm count by increasing gonadotrophin, T/E2 and testosterone levels. [2][3][4] Because the literature is in agreement with the data presented here, we can confirm that letrozole increased the sperm count in dispermic patients with T/E2 ,10.…”
Section: Letrozole For Azoospermia and Cryptozoospermia G Cavallini Esupporting
confidence: 81%
“…Furthermore, the number of the patients studied is similar or even higher than that reported in previous studies. [2][3][4][5][6] Our data show that BMI and the T/E2 ratio were not strictly equivalent in predicting the results of active drug administration or spermatogenesis impairment, even though BMI is closely associated with the T/E2 ratio and spermatogenesis. 20,21 Interestingly, these data were in agreement with the previous results of Raman and Schlegel, where obese patients did not have a greater benefit of treatment than other patients, even though aromatase from adipose tissue could increase aromatase activity.…”
Section: Letrozole For Azoospermia and Cryptozoospermia G Cavallini Ementioning
confidence: 89%
See 3 more Smart Citations